A RARE COMPLICATION: ACUTE RESPIRATORY DISTRESS SYNDROME (ARDS) INDUCED BY SEVERE PNEUMOCYSTIS CARINII PNEUMONIA (PCP) - Prasetya Wijaya, Gede Adi; Yanti, Andi (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Introduction: Pneumocystis pneumonia (PCP) represents a prevalent opportunistic infection among individuals with HIV, posing a significant risk of mortality. The occurrence of acute respiratory distress syndrome (ARDS) as a consequence of PCP further accentuates the gravity and intricacy of this pulmonary infection. Objective: This case report aims to discuss the management of the rare complication of ARDS induced by severe PCP in a 36-year-old man with HIV. Case Presentation: A 36-year-old male teacher, presented with worsening dyspnea, intermittent fever, and a productive cough persisting for two weeks, along with weight loss and fatigue. Initial diagnostic impressions included pulmonary tuberculosis with pneumonia. Treatment involved oxygen therapy, fluid administration, and medication. Laboratory tests showed leukocytosis, elevated blood glucose, and abnormal liver function. Subsequent investigations confirmed HIV infection. Chest X-ray revealed severe bilateral pneumonia and possible ARDS, leading to transfer to the Intensive Care Coronary Unit for further management. Discussion: The diagnosis of severe Pneumocystis jirovecii pneumonia (PCP) underscores the importance of recognizing PCP as a significant clinical concern, especially in HIV patients. Diagnostic challenges, such as late HIV diagnosis, highlight the need for timely screening and intervention. Management involved a multidisciplinary approach, including pulmonologists and cardiologists. Despite treatment adjustments, some patients experience clinical deterioration, necessitating careful management strategies like antiretroviral (ARV) therapy and respiratory support. This case underscores the complexity of managing PCP-related ARDS and the crucial role of timely intervention and comprehensive care. Conclusion: Severe PCP led to ARDS in an HIV-infected patient due to inflammation and lung damage, exacerbated by the immunocompromised state. Timely diagnosis and treatment are crucial to prevent complications and improve outcomes in such cases.